F FIVE MINUTE EXERCISE UNTUK REMAJA JOMPO - yani, fitri; Devinta Yulia Laksmita (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The prevalence of lower extremity musculoskeletal disorders is quite high among adults, causing a heavy burden for individuals, families and workplaces. Musculoskeletal disorders not only cause pain or discomfort, but also limitations in daily activities. Pain and limitations in daily activities have a broad impact on the sufferer's quality of life and emotional state. Strength training done regularly has been proven to reduce musculoskeletal pain and reduces a person's risk of developing musculoskeletal disorders. Based on this background, it is necessary to take action by providing exercise or five minute exercise as a preventive and curative effort to prevent serious musculoskeletal disorders in the future and physical exercise can also increase a person's fitness level. The aim of this activity is a form of preventive effort and can also be curative for problems during lectures. Mandatory outputs from this program are journal articles, mass media articles, and activity videos. Apart from that, the additional output is an IPR-enabled exercise video.